2001
DOI: 10.1007/s004360000296
|View full text |Cite
|
Sign up to set email alerts
|

Genetic immunization with plasmid DNA coding for the ROP2 protein of Toxoplasma gondii

Abstract: The ROP2 protein of Toxoplasma gondii has previously been proposed as a vaccine candidate against toxoplasmosis. In this work we characterize the immune response induced by injection of plasmid DNA coding for this protein in three strains of mice (BALB/c, C57BL/6, and CBA/J) displaying different levels of susceptibility to toxoplasmosis and compare it with that obtained by vaccination with the live attenuated ts-4 strain of T. gondii. The ROP2 gene was cloned in the eukaryotic expression vector pcDNA3 and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 30 publications
6
36
0
2
Order By: Relevance
“…TSA2 was obtained from the Wiktor strain of T. gondii as described elsewhere (41). The temperature-sensitive mutant ts-4 strain of T. gondii was maintained in human skin fibroblasts at 33°C as previously described (25).…”
Section: Methodsmentioning
confidence: 99%
“…TSA2 was obtained from the Wiktor strain of T. gondii as described elsewhere (41). The temperature-sensitive mutant ts-4 strain of T. gondii was maintained in human skin fibroblasts at 33°C as previously described (25).…”
Section: Methodsmentioning
confidence: 99%
“…Apart from SAG1, other T. gondii proteins have also been tested (12,16,28,29,33,34,39,49). Recombinant GRA4 (rGRA4) combined with cholera toxin induced partial protection in C57BL/6 immunized mice against a nonlethal challenge with the 76,000-molecular-weight T. gondii strain (33).…”
mentioning
confidence: 99%
“…Several trials of DNA-based vaccines against toxoplasmosis have been conducted, mainly with mice and various T. gondii antigens, such as membrane-associated surface antigen SAG1 (5,32), excreted-secreted dense-granule proteins GRA1 (33,38), GRA7 (38), and GRA4 (18), and rhoptry proteins ROP2 (29,38) and ROP1 (14). These trials have been encouraging, in that they have demonstrated the development of different levels of protection in mice.…”
mentioning
confidence: 99%